Pengaruh Manajemen Risiko dan Tata Kelola Perusahaan terhadap Kinerja Perbankan - Hetty; Siti Rahmayuni; Anwar Arifin Pinem; Nabila (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze the effect of risk management and corporate governance on banking performance. The research employs a quantitative approach using secondary data obtained from banks’ annual reports during the observation period. Data analysis is conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the WarpPLS application to examine latent and nonlinear relationships among variables. The results indicate that risk management has a positive and significant effect on banking performance, suggesting that effective risk management practices are able to enhance bank stability and operational efficiency. Corporate governance is also proven to have a positive effect on banking performance through improvements in transparency, accountability, and the effectiveness of supervision. The novelty of this study lies in the use of WarpPLS to analyze nonlinear relationships between risk management, corporate governance, and banking performance, which remains limited in banking research in Indonesia.